Construction of Judicial Rules for the System of Retaining and Maintaining Relatives and the System of Residential Surveillance from the Perspective of Reducing Punishment - Li, Xinhang (Transactions on Social Science, Education and Humanities Research, 2023)
China's residential surveillance system does not take into account the need for criminal suspects to support their parents. Specifically, the setting of the residential surveillance system has certain deficiencies in the face of family warmth and indoctrination, the traditional idea of filial piety, and compensation for the victimized family, while the ancient Chinese system of surviving and raising relatives provides three perspectives for improving the residential surveillance system: one is to reform criminals based on the democratization of the judiciary, the other is to inherit the civilization of etiquette based on the Chinese style of rule of law, and the third is to conform to the idea of conforming to the punishment based on the rule of law of human rights, so as to guide the exploration of judicial rules for the construction of the residential surveillance system. Under the premise of fully integrating the idea of surviving and supporting relatives, the possible direction of the judicial rules of the residential surveillance system is: when reviewing a criminal suspect's application for residential surveillance based on the detention system, starting from the theory of social danger and the theology of the victim, the investigation of the number of children, identity relationship, and ability to adopt relatives at the family level of the surviving entity is carried out, and when carrying out residential surveillance, the right to know of community neighbors and the privacy of the adoptive entity should be guaranteed, and when criminal suspects violate the provisions on residential surveillance, their qualifications for retention should be revoked and the punishment for failure to be fulfilled. Apply the idea of retention to the residential surveillance system, so as to promote the revival of China's excellent traditional legal culture and achieve the goal of good law and good governance.